An appraisal of women slavery in the philosophy of Simone de beauvoir's second sex - Mbaegbu, Celestine Chukwuemeka (Journal of religion and human relations, 2016)
Slavery is one of the humanistic concepts bothering the human society. Slavery can be seen as a state in which ones life and affairs are controlled by another; hence the slave is seen as a lesser being. Simone de Beauvoir demonstrates how patriarchy, motherhood, religion and culture enslave women. The interest of this article is on the basic ideas of Simone de Beauvoir on the inhuman treatment meted out to women who are humans too and therefore advocates for the abolishment of the traditional institution. Using philosophical analysis, it is revealed that women are indeed oppressed in nearly all cultures. The instruments of un-freedom stem from Christian, patriarchal, reproductive, marital, family, dependency and cultural orientation factors. And the conclusion is that though women are the major players that underscore their development, liberation and enhancement, especially when they do not rally round to form a formidable team, refuse to help one another and cherish being harsh and antagonistic to one another, their emancipation and liberation from serfdom or thralldom would be a mirage. That notwithstanding, women should be treated as persons, with voluntas and ratio, because when there is mutual relationship and respect between humans, there would be enhancement of values, peace and development in the society.